The Difference of Clinical Characteristics Between Patients With Exon 19 Deletion and Those With L858R Mutation in Nonsmall Cell Lung Cancer. Issue 44 (November 2015) - Zhang, Yaxiong; He, Dacheng; Fang, Wenfeng; Kang, Shiyang; Chen, Gang; Hong, Shaodong; Sheng, Jin; Zhan, Jianhua; Chen, Nan; Hu, Zhihuang; Xue, Cong; Yang, Yunpeng; et al.
Abstract : Abstract: Recent studies have demonstrated that exon 19 deletion (19 Del) and exon 21 L858R mutation (L858R) are 2 different types of sensitive epidermal growth factor receptor (EGFR) mutations in nonsmall cell lung cancer (NSCLC). However, whether there are some differences between those 2 groups in baseline clinical characteristics is still unclear. We enrolled consecutive 1271 NSCLC patients detected with either 19 Del or L858R and collected their baseline clinical characteristics including age, sex, comorbidity, smoking and drinking status, body mass index (BMI), TNM stage, histologic type, differentiation, tumor maximum diameter (TMD), and CEA level. χ 2 test and multivariate logistic regression analysis were used to compare the difference. We found a higher percentage of 19 Del in younger patients group (< = 50 yr) than L858R ( P < 0.001) through χ 2 test. Besides, patients with 19 Del have higher risk of lymph node metastasis ( P < 0.001). However, there were no significant differences in other items of clinical characteristics between 19 Del and L858R. Multivariate analysis showed similar significant results. Subgroup analysis in different age groups (10 yr as an interval) and N stages (stratified by N0, N1, N2, and N3) also indicated above-mentioned trends. NSCLC patients with 19 Del are more likely to be young and have lymphatic metastasis than those with L858R. Age and N stage might be considered in predicting EGFR mutation type in NSCLC.